2023
DOI: 10.3389/fpubh.2023.1036172
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychological capital and depressive symptoms during COVID-19: The mediating role of perceived social support and the moderating effect of employment pressure

Abstract: IntroductionThe Coronavirus Disease 2019 (COVID-19) pandemic affects individuals' mental health that can result in fear of getting COVID-19 infection and depression. Prior research has demonstrated that both psychological capital and perceived social support are related to the severity of depression. Yet no study explored the direction of associations between these factors. This undermines the validity of psychological capital as a basis for health interventions.MethodsThis study aimed to explore the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Positive emotions can lead individuals to a growth trajectory, enabling them to identify and build their resources, and these resources are enduring (87). As an inherent positive psychological resource within individuals, multiple studies (95,96) have confirmed that individuals with high levels of PsyCap generally perceive more prominent material and emotional support between family members and peers, which provides support for the build hypothesis in the broaden-and-build theory. Furthermore, the burnout experienced by medical staff can lead to a decrease in positive psychological resources such as low hope levels and low self-efficacy.…”
Section: Mediation Effects Of Psycap and Pssmentioning
confidence: 79%
“…Positive emotions can lead individuals to a growth trajectory, enabling them to identify and build their resources, and these resources are enduring (87). As an inherent positive psychological resource within individuals, multiple studies (95,96) have confirmed that individuals with high levels of PsyCap generally perceive more prominent material and emotional support between family members and peers, which provides support for the build hypothesis in the broaden-and-build theory. Furthermore, the burnout experienced by medical staff can lead to a decrease in positive psychological resources such as low hope levels and low self-efficacy.…”
Section: Mediation Effects Of Psycap and Pssmentioning
confidence: 79%
“…Several subsequent studies have further reinforced these findings by showcasing the beneficial relationship between PsyCap and a wide array of outcomes, including creative and innovative performance, job role effectiveness, productivity, career advancement, work engagement, happiness, reduced absenteeism, and sustained job satisfaction ( Avey et al, 2008 ; Peterson et al, 2011 ; Rego et al, 2012 ; Luthans et al, 2013 ; Bouckenooghe et al, 2015 ; Huang and Luthans, 2015 ; Williams et al, 2015 ; Youssef-Morgan and Luthans, 2015 ; Baykal and Zehir, 2018 ; Du Plessis and Boshoff, 2018 ; Järlström et al, 2020 ; Karakitapoğlu-Aygün et al, 2020 ; Özsungur, 2020 ). Additionally, studies have demonstrated PsyCap’s negative association with turnover intention, stress, and depressive symptoms ( Avey et al, 2009 ; Huang et al, 2023 ). Further exploration into PsyCap’s influence has uncovered its role as both a mediator and a moderator in various organizational contexts.…”
Section: Psycap and The Cross-over Effectmentioning
confidence: 99%
“…Positive emotions can lead individuals to a growth trajectory, enabling them to identify and build their resources, and these resources are enduring (87). As an inherent positive psychological resource within individuals, multiple studies (95,96) have confirmed that individuals with high levels of PsyCap generally perceive more prominent material and emotional support between family members and peers, which provides support for the build hypothesis in the broaden-and-build theory. Furthermore, the burnout experienced by medical staff can lead to a decrease in positive psychological resources such as low hope levels and low self-efficacy.…”
Section: Mediation Effects Of Psycap and Pssmentioning
confidence: 79%